Does selenium offset methylmercury toxicity across trophic levels in a primary producer, Auxenochlorella pyrenoidosa, and a detritovore, Aeolosoma variegatum? - Husnah Azmi; Stephanie J. Melles; Andrew E. Laursen (FACETS)
Methylmercury ([CH3Hg]+ or MeHg) is a potent neurotoxin that impairs functioning of the nervous system, and selenium (Se) is known to provide a protective effect against MeHg. Experiments were run to investigate the expected offsetting of MeHg toxicity by Se across trophic levels at the base of the aquatic food chain. An algal primary producer, Auxenochlorella pyrenoidosa, was exposed to MeHg (2 µg L−1) in the presence or absence of varying levels of Se (0 µg L−1, 2 µg L−1, and 5 µg L−1). Results showed that MeHg decreased the maximum density of Auxenochlorella, which Se did not offset. Equal amounts (8 mg) of the algal biomass produced under exposure conditions were subsequently fed to a detritovore, Aeolosoma variegatum (a small freshwater annelid worm). When consuming dietary Se in MeHg contaminated water, or when consuming dietary Se with dietary MeHg, Aeolosoma populations experienced a rescue effect against MeHg, i.e., they achieved greater final population density. Understanding safe levels of dietary Se that provide population level protection against MeHg is a critical step towards managing mercury in contaminated ecosystems.